Preparation and in vitro characterization of laminarin based hydrogels - SEZER, ALİ DEMİR; CÖMEZ, BİRNUR; EKENTOK ATICI, CEYDA (MARMARA UNIV, 2021)
Hydrogels are one of the most effective pharmaceutical forms because of several advantages in the treatment of burn and wound headings. Laminarin is a storage polysaccharide derived from brown algae and member of the 1-3-beta-D-glucan family. It is a heparin-like molecule and plays role in hemoslasis, regulation of cell growth and regeneration. Also, indirectly functional in neovascularizalion. In addition, accelerates the formation of fibroblast activity and re-epithelization. Aim of this study is prepare laminarin hydrogels and evaluate the ill vitro characteristics of hydrogels for use in various wounds. For this purpose, different hydrogel formulations prepared and examined, and evaluated by water absorption Ca racily, viscosity, rheological and mechanical properties and bioadhesion. II was observed that hydrogels prepared with laminarin are an ideal wound dressing as expected.
Keywords: Hydrogel; laminarin; carboxymethylcellulose; polyvinylpyrrolidone; wound healing; STABILITY; ANTITUMOR; CELLULOSE; PVP